Primary Outcome Evaluation of a Next-Generation Left Atrial Appendage Closure Device: Results From the PINNACLE FLX Trial. Issue 18 (6th April 2021) - Kar, Saibal; Doshi, Shephal K.; Sadhu, Ashish; Horton, Rodney; Osorio, Jose; Ellis, Christopher; Stone, James; Shah, Manish; Dukkipati, Srinivas R.; Adler, Stuart; Nair, Devi G.; Kim, Jamie; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Left atrial appendage (LAA) occlusion provides an alternative to oral anticoagulation for thromboembolic risk reduction in patients with nonvalvular atrial fibrillation. Since regulatory approval in 2015, the WATCHMAN device has been the only LAA closure device available for clinical use in the United States. The PINNACLE FLX study (Protection Against Embolism for Nonvalvular AF Patients: Investigational Device Evaluation of the Watchman FLX LAA Closure Technology) evaluated the safety and effectiveness of the next-generation WATCHMAN FLX LAA closure device in patients with nonvalvular atrial fibrillation in whom oral anticoagulation is indicated, but who have an appropriate rationale to seek a nonpharmaceutical alternative. Methods: This was a prospective, nonrandomized, multicenter US Food and Drug Administration study. The primary safety end point was the occurrence of one of the following events within 7 days after the procedure or by hospital discharge, whichever was later: death, ischemic stroke, systemic embolism, or device- or procedure-related events requiring cardiac surgery. The primary effectiveness end point was the incidence of effective LAA closure (peri-device flow ≤5 mm), as assessed by the echocardiography core laboratory at 12-month follow-up. Results: A total of 400 patients were enrolled. The mean age was 73.8±8.6 years and the mean CHA2 DS2 -VASc score was 4.2±1.5. The incidence of the primary safety end point was 0.5% with a 1-sided 95% upper CI of 1.6%, meeting the performance goal of 4.2% ( P <0.0001). The incidence of the primary effectiveness end point was 100%, with a 1-sided 95% lower CI of 99.1%, again meeting the performance goal of 97.0% ( P <0.0001). Device-related thrombus was reported in 7 patients, no patients experienced pericardial effusion requiring open cardiac surgery, and there were no device embolizations. Conclusions: LAA closure with this next-generation LAA closure device was associated with a low incidence of adverse events and a high incidence of anatomic closure. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02702271.